2020
DOI: 10.1007/s15010-020-01536-y
|View full text |Cite
|
Sign up to set email alerts
|

Selective toxicity of antibacterial agents—still a valid concept or do we miss chances and ignore risks?

Abstract: Background Selective toxicity antibacteribiotics is considered to be due to interactions with targets either being unique to bacteria or being characterized by a dichotomy between pro- and eukaryotic pathways with high affinities of agents to bacterial- rather than eukaryotic targets. However, the theory of selective toxicity oversimplifies the complex modes of action of antibiotics in pro- and eukaryotes. Methods and objective This review summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 408 publications
(576 reference statements)
0
24
0
2
Order By: Relevance
“…Antibacterial agents refer to products obtained from microorganisms such as bacteria, actinomycetes, and fungi in culture and also include various antibiotics, sulfonamides, imidazoles, nitroimidazoles, quinolones, and other chemically synthesized drugs [ 7 ]. Antimicrobial drugs have inhibitory and killing effects on pathogens at certain concentrations and are widely used in clinical practice [ 8 ]. Related studies have shown that the relationship between the use of antimicrobial drugs and bacterial resistance may provide guidance for the use of antimicrobial drugs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antibacterial agents refer to products obtained from microorganisms such as bacteria, actinomycetes, and fungi in culture and also include various antibiotics, sulfonamides, imidazoles, nitroimidazoles, quinolones, and other chemically synthesized drugs [ 7 ]. Antimicrobial drugs have inhibitory and killing effects on pathogens at certain concentrations and are widely used in clinical practice [ 8 ]. Related studies have shown that the relationship between the use of antimicrobial drugs and bacterial resistance may provide guidance for the use of antimicrobial drugs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 2hydroxyethyl (14j) derivative was found to show potent antimicrobial activity against VanA resistant Enterococcus faecium strains isolated from urine, blood culture, drain and wound. Although the 50S ribosomal subunit occurs only in prokaryotes, antibiotics that inhibit protein synthesis by binding to the 50S subunit-as pleuromutilin derivates do-may be severely toxic to eukaryotes [36]. Therefore, it is essential to perform in vitro and in vivo toxicological studies of the active derivatives in the future.…”
Section: Discussionmentioning
confidence: 99%
“…ENX is a 1,8-naphthyridine derivative of 1,4-dihydro-1,8naphthyridine with an ethyl group at the 1 position, a carboxy group at the 3-position, an oxo-substituent at the 4-position, a fluorine-substituent at the 5-position and a piperazin-1-yl group at the 7 position. Enoxacin inhibits bacterial DNA gyrase and topoisomerase IV [7,8]. Reports concerning its ability to interfere with human topoisomerase are contrary [1,[8][9][10] and it seems that this interaction is concentration-dependent [8].…”
Section: Introductionmentioning
confidence: 99%
“…Enoxacin inhibits bacterial DNA gyrase and topoisomerase IV [7,8]. Reports concerning its ability to interfere with human topoisomerase are contrary [1,[8][9][10] and it seems that this interaction is concentration-dependent [8].…”
Section: Introductionmentioning
confidence: 99%